ABORTION OF A DEFORMED FETUS IN THE PERSPECTIVE OF MASLAHAH MURSALAH - Diansyah, Erry Nur; Fadhilah, Iman; Hikmah, Nur; Ramadani, Desma Gautrin (Pascasarjana Universitas Wahid hasyim Semarang, 2021)
This study aims to reveal the legal excavations that allow abortion of a fetus with defects with mursalah maslahah. Basically, fetal abortion is forbidden, but because the times have brought us to a condition where we can see the condition of the fetus in the womb, under certain conditions, abortion is permissible. This research is a qualitative research study of literature using descriptive analysis of content analysis (content analysis). In this study, it was shown that the permissible abortion of a fetus with defects in the perspective of maslahah mursalah had fulfilled three conditions, namely; are in accordance with the objectives of the Shari'ah, are rational and definite, for the public interest. As well as in the use of maslahah mursalah as an istimbat al-ahkam method, it can be used when problems are not found or resolved in the texts, the opinion of the Medina experts, ijma' friends, Qiyas, istihsan then after that maslahah mursalah is used which in the case of abortion of a deformed fetus has fulfilled all aspects and produce a law that allows abortion of a defective fetus if the spirit has not yet been breathed into the fetus.